Gran capacidad de adaptación de las bibliotecas: 3 informes de OCLC - Anglada, Lluís (Anuario ThinkEPI, 2015)
Reseñas de los informes: Connaway, Lynn-Silipigni;Â Faniel, Ixchel (2014). Reordering Ranganathan: Shifting user behaviors, shifting priorities. Dublin, OH: OCLC Research. http://goo.gl/S00GHf Â OCLC (2014). At a tipping point: Education, learning and libraries: a report to the OCLC membership. Dublin, OH: OCLC. http://goo.gl/BpPHYZ Â OCLC (2014). Optimizing your library´s return on technology investment. OCLC EMEA. http://goo.gl/hcvgmn